Ibn Sina’s Philosophical Thought: Emanation Theory, the Soul, and al-Wujūd - Abdul Kadir; Mega Rahmayani AS; Saripa Balqis Alqadri; Mahmuddin M; Nurlaelah Abbas; Muh. Japri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Avicenna’s philosophical thought occupies an important position in the development of Islamic philosophy, particularly in the fields of metaphysics and the nature of knowledge. Three main concepts that form the foundation of his philosophy are emanation, the soul, and al-wujūd (being), which are employed to explain the relationship between God, the universe, and human beings in a rational and systematic manner. This study aims to analyze Avicenna’s philosophical thought by highlighting the concept of emanation as a theory of the origin of existence, the concept of the soul in understanding human nature, and the concept of al-wujūd as the ontological basis of his philosophy. This research adopts a qualitative approach using a library research method. Data are collected from primary sources in the form of Avicenna’s major works and secondary sources such as relevant books and scholarly journal articles. Data analysis is conducted using a descriptive-analytical method to examine the interrelationship and characteristics of these three concepts within the framework of Islamic philosophy. The findings indicate that Avicenna successfully developed an integrative philosophical system that harmonizes philosophical rationality with Islamic values, thereby making a significant contribution to the development of the Islamic intellectual tradition and subsequent philosophical thought.